2014
DOI: 10.1002/cctc.201402631
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Encapsulation of Neutral Diazoacetate Esters and Catalyzed 1,3‐Dipolar Cycloaddition Reaction by a Self‐Assembled Hexameric Capsule

Abstract: Diazoacetate esters proved to be suitable neutral guests for\ud the self-assembled resorcin[4]arene hexameric capsule. The hydrogen- bonded supramolecular host catalyzed the 1,3-dipolar cycloaddition reaction between diazoacetate esters and electron- poor alkenes such as acrolein, acrylonitrile, crotonaldehyde, trans-2-hexenal, methyl, and butyl acrylate,\ud which led to the corresponding 4,5-dihydro-1H-pyrazole\ud derivatives. The cycloaddition reaction occurred within the\ud cavity of the capsule. In fact, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 63 publications
0
24
0
Order By: Relevance
“…Their carbene-like character prompted their employment as potential substrates for the hexamer capsule. Scarso and coworkers investigated their encapsulation in the resorcin [4] arene assembly and found that the efficient capsule catalyzed 1,3-dipolar cycloaddition between diazoacetate esters and electron-poor alkenes, leading to 4,5-dihydro-1H-pyrazole derivatives [57]. It is worth noting that Diels-Alder reactions are among the most investigated chemical transformations, displaying the effects of supramolecular unimolecular, or self-assembled capsules in water [58,59], while examples in organic solvents are rare apart from the seminal work of Rebek [15].…”
Section: C─c Bond-forming Reactionsmentioning
confidence: 99%
“…Their carbene-like character prompted their employment as potential substrates for the hexamer capsule. Scarso and coworkers investigated their encapsulation in the resorcin [4] arene assembly and found that the efficient capsule catalyzed 1,3-dipolar cycloaddition between diazoacetate esters and electron-poor alkenes, leading to 4,5-dihydro-1H-pyrazole derivatives [57]. It is worth noting that Diels-Alder reactions are among the most investigated chemical transformations, displaying the effects of supramolecular unimolecular, or self-assembled capsules in water [58,59], while examples in organic solvents are rare apart from the seminal work of Rebek [15].…”
Section: C─c Bond-forming Reactionsmentioning
confidence: 99%
“…For the design of new artificial enzyme-like catalysts, it is of fundamental importance to understand the prerequisites for catalytic activity. We 2 and others 3 have shown that the hexameric resorcinarene capsule I , 4 which self-assembles from six units of resorcinarene 1 and eight water molecules (Fig. 1), is an efficient catalyst for a variety of cationic reactions.…”
mentioning
confidence: 93%
“…[35] If ethyl diazoacetate (44)a nd acrolein (45)w ere reacted inside the cavity of CR 6 ,p roduct 46 wasf ormed in 47 %y ield, whereas, in the bulk solvent, in the absence of CR 6 ,o nly a 12 %y ield was obtained. [35] The presence of neutral guest 44 inside CR 6 was confirmed by means of NMR spectroscopy.I f44 was added to aw ater-saturated solution of CR 6 in CDCl 3 ,t hen new resonancesa tn egative values appeared in the upfield region of the 1 HNMR spectrum.A nalogous results were observedw ith tert-butyl diazoacetate and benzyld iazoacetate. Also, in this case, the encapsulationo fd iazoacetatei nside CR 6 was rationalized on the basis of stabilization imparted by the electron-rich internal surfaceo ft he capsule on the carbenelike guest.…”
Section: Brønsted Acid and Cation···p Catalysismentioning
confidence: 99%